An Ethical Analysis of the Engineering Profession on Progressive Structural Failure: A Case Study of the Collapse of Champlain Towers South, Surfside, Florida - Mahesha Gani Tarigan (International Journal of Science and Environment (IJSE), 2026)
The tragic collapse of Champlain Towers South (CTS) in Surfside, Florida, on June 24, 2021, was a progressive structural failure that killed 98 people and became one of the most significant civil engineering disasters in recent decades. Engineering investigations indicated that the failure initiated in the transfer slab and pool deck area, which experienced severe degradation due to waterproofing failure, chloride penetration, reinforcement corrosion, and spalling, which reduced the load-bearing capacity of the elements. A 2018 report by Morabito Consultants identified “major structural damage” to the slab and columns above the underground garage, but repair recommendations were not promptly implemented by the building owner. This delay was exacerbated by inconsistent subsequent technical interpretations and ineffective risk communication. This study evaluates the CTS tragedy through an engineering ethics approach using the Indonesian Engineers Association (PII) Code of Ethics framework, including Sapta Dharma and Catur Karsa, as well as the theories of deontology, utilitarianism, and virtue ethics. The analysis results show that the engineer's obligation to prioritize public safety (duty to warn) takes higher priority than contractual obligations to the client. Failure to formally escalate to regulators when a building owner fails to respond to critical findings constitutes an ethical violation that contributed to the lack of mitigation before progressive collapse. Furthermore, indications of conflict of interest and a lack of professional rigor worsen the quality of technical decision-making. As a practical contribution, this study proposes the implementation of a “Structural Hazard Mandatory Reporting Protocol” that includes imminent hazard criteria, a tiered reporting mechanism, response deadlines, and protections for reporting engineers. This study emphasizes the importance of integrity, moral courage, and improved structural inspection standards to prevent similar failures in the future.